Temporal evolution of cadmium, copper and lead concentration in the Venice Lagoon water in relation with the speciation and dissolved/particulate partition. Issue 2 (April 2018) - Morabito, Elisa; Radaelli, Marta; Corami, Fabiana; Turetta, Clara; Toscano, Giuseppa; Capodaglio, Gabriele
Abstract: In order to study the role of sediment re-suspension and deposition versus the role of organic complexation, we investigated the speciation of cadmium (Cd), copper (Cu) and lead (Pb) in samples collected in the Venice Lagoon during several campaigns from 1992 to 2006. The increment in Cd and Pb concentration in the dissolved phases, observed in the central and northern basins, can be linked to important alterations inside the lagoon caused by industrial and urban factors. The study focuses on metal partition between dissolved and particulate phases. The analyses carried out in different sites illustrate the complex role of organic matter in the sedimentation process. While Cd concentration in sediments can be correlated with organic matter, no such correlation can be established in the case of Pb, whose particulate concentration is related only to the dissolved concentration. In the case of Cu, the role of organic complexation remains unclear. Graphical abstract: Highlights: Salinity, biological processes and physical phenomena, control fate of metals. Role of organic matter in the sedimentation process is complex. Metal complexation by organic ligands increases the mobility of metals. Metal concentrations can be related to the sediment resuspension.